LIQUID SULFUR AT THE BOTTOM OF A THERMAL LAKE IN THE UZON CALDERA, KAMCHATKA - Karpov G.A.; Fazlullin S.M.; Nadezhnaya T.B. (My University, 1996)
A local petro-hydrothermal liquid sulfur - gas - water - rock system was formed at the bottom of a thermal lake situated within the present-day ore-forming hydrothermal system of the Uzon Caldera (East Kamchatka) after a vigorous steam-water exposion in 1989. A crust of native sulfur was found under a layer of subacid low-saline water at a depth of 25-25.5 m. A zone of liquid sulfur exists at a depth of 25.5 to 32.5 m. This zone is characterized by a temperature of 116 to 142°C, a high hydrogen sulfide content, and fluctuations in the composition of spontaneous gases emanating in the zone of thermal activation. The thermal energy of the system was calculated to estimate the duration of liquid sulfur life.